2010
DOI: 10.1186/1757-1626-3-82
|View full text |Cite
|
Sign up to set email alerts
|

Acute occlusion of the celiac axis and its branches with perforation of gastric fundus and splenic infarction, findings on spiral computed tomography: a case report

Abstract: We present the contrast-enhanced spiral CT findings in a case of acute celiac artery occlusion with gastric perforation and total splenic infarction. Spiral CT depicted thrombus in the celiac axis and its branches, stenosis of the superior mesenteric artery, splenic infarction and lack of enhancement of the gastric wall with a large necrotic gap. Spiral CT enabled prompt diagnosis and therapy in this rare condition in a patient with suspicion of acute mesenteric ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In our case, the anatomical variation of the common hepatic artery arising directly from the aorta and not branching from the celiac trunk saved the liver. Gastric ischemia is uncommon as the stomach has a rich blood supply from branches of the celiac trunk and the SMA collaterals [ 6 ]. Kelekis Nl et al reported a case of gastric fundus perforation in a patient with extensive thrombus in the celiac trunk and its branches with coexisting stenosis of the origin and proximal SMA that might have contributed to the development of irreversible gastric ischemia and necrosis [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our case, the anatomical variation of the common hepatic artery arising directly from the aorta and not branching from the celiac trunk saved the liver. Gastric ischemia is uncommon as the stomach has a rich blood supply from branches of the celiac trunk and the SMA collaterals [ 6 ]. Kelekis Nl et al reported a case of gastric fundus perforation in a patient with extensive thrombus in the celiac trunk and its branches with coexisting stenosis of the origin and proximal SMA that might have contributed to the development of irreversible gastric ischemia and necrosis [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…(6) Hepatic ischaemia is also uncommon, as the liver has a dual blood supply from both the hepatic artery and the portal venous system.…”
Section: Discussionmentioning
confidence: 99%